Core decompression vs. allogenic non-vascularized bone grafting in patients with osteonecrosis of the femoral head - Mei, Jin; Jiang, Zai-ping; Pang, Li-li; Huang, Yingtao; Gong, Yu; Zhu, Jun; Zhang, Ling-wei (Frontiers in Surgery, 2023)
Core decompression and allogenic non-vascularised bone grafting are used in the early stage of osteonecrosis of femoral head for a period. Since the comparison of the core decompression and allogenic non-vascularised bone grafting are less reported, the purpose of our study was to investigate the difference of two procedures in patients with the osteonecrosis of femoral head.Between January 2018 and January 2019, 59 patients (64 hips) are divided into core decompression group and non-vascularized bone grafting group according to their procedures. The radiographic survival rates are 76.9% and 77.3% in the two groups. The VAS of core decompression group was 6.08 ± 1.164 before operation and 3.30 ± 1.431 two years after operation (p<0.05); The VAS of allogenic non-vascularized bone grafting group was 6.00 ± 1.209 before operation and 3.15 ± 1.537 two years after operation (p<0.05). The Harris hip score of the core decompression group was 52.49 ± 6.496 before operation, and increased by 81.14 ± 8.548 two years after operation (p<0.05); The Harris hip score of allogenic non-vascularized bone grafting group was 53.56 ± 5.925 before operation and 81.33 ± 7.243 two years after operation (p<0.05). In the core decompression group, BMI>25 was correlated with the collapse of femoral head or conversion to THA (p<0.05; 95% confidence interval [CI], 0.006-1.334), and Arco III was correlated with the collapse of femoral head or conversion to THA (p<0.05; 95% confidence interval [CI], 2.514-809.650). In allogenic non-vascularized bone grafting group, age, BMI, and ARCO stage are significantly associated with the collapse of femoral head or THA (p>0.05).There was no significant difference in radiographic survival rate of femoral head between the two groups. Both groups can alleviate pain and improve functional of patients, but there is no significant difference in the degree of improvement. In the core decompression group, BMI>25 and Arco III are correlated with the collapse of femoral head or conversion to THA. In allogenic non-vascularized bone grafting group, no association was found between age, BMI and ARCO stage and collapse of femoral head or conversion to THA.